2005
DOI: 10.1016/j.jmwh.2005.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing and the Family

Abstract: The family experience of genetic testing is explored in this article. Two family stories are presented to illustrate how families define and manage the ethical and social issues that emerge during 2 types of genetic testing: mutation analysis for Huntington's disease and genetic testing for breast and ovarian cancer susceptibility. These 2 families were purposefully selected because their stories exemplify the complexity of the genetic testing experience. In addition, the story of the family living with Huntin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Some studies have reported that siblings show transient anxiety and depression after carrier testing. [20][21][22][23] Most studies assessing adolescent or childhood carrier testing are small and address individuals with a family history of X-linked conditions (e.g., Duchenne muscular dystrophy, hemophilia, and fragile X syndrome) and autosomal-recessive conditions; Borry et al provide a summary of some of the early literature in this area. 18,24 These small studies documented high short-term recall and a number of potentially beneficial psychosocial outcomes, including relief in those who are non-carriers, relief from uncertainty in both carriers and non-carriers, and positive reappraisal of self-esteem and self-image.…”
Section: Carrier Testing Of Adolescentsmentioning
confidence: 99%
“…Some studies have reported that siblings show transient anxiety and depression after carrier testing. [20][21][22][23] Most studies assessing adolescent or childhood carrier testing are small and address individuals with a family history of X-linked conditions (e.g., Duchenne muscular dystrophy, hemophilia, and fragile X syndrome) and autosomal-recessive conditions; Borry et al provide a summary of some of the early literature in this area. 18,24 These small studies documented high short-term recall and a number of potentially beneficial psychosocial outcomes, including relief in those who are non-carriers, relief from uncertainty in both carriers and non-carriers, and positive reappraisal of self-esteem and self-image.…”
Section: Carrier Testing Of Adolescentsmentioning
confidence: 99%
“…While benefits such as diagnostic certainty and greater awareness of prophylactic treatment and risk stratification may be achieved, genetic testing may also contribute to an increase in risk for depression, anxiety, guilt, stigmatization, discrimination, family conflict, and unnecessary or inappropriate use of risk-reducing strategies29. Therefore, it is imperative that patients are well informed on genetic testing implications and must not be coerced into providing a sample for genetic analysis.…”
Section: Ethical Legal and Societal Implicationsmentioning
confidence: 99%
“…Genetic testing should be considered both a family and individual experience29. While genetic testing is performed on an individual’s genetic material, both the individual’s decision to undergo genetic testing and that individual’s test results may have substantial implications for other family members, especially in sudden cardiac death related disorders.…”
Section: Ethical Legal and Societal Implicationsmentioning
confidence: 99%
“…Since acquiring and disseminating accurate information regarding familial disease risk is a key component of the genetic counseling enterprise, intra-family communication has been investigated extensively (Kenen et al 2004b; Peterson et al 2003; Suthers et al 2006; Tercyak et al 2002; Tercyak et al 2007; Van Riper 2005). The present study builds on this work as well as our own prior studies (Kenen et al 2001; Kenen and Peters 2001; Koehly et al 2009; Peters et al 2006).…”
Section: Introductionmentioning
confidence: 99%